Activation of p62/SQSTM1–Keap1–Nuclear Factor Erythroid 2-Related Factor 2 Pathway in Cancer - Ichimura, Yoshinobu; Komatsu, Masaaki (Frontiers in Oncology, 2018)
Autophagy and the Keap1-Nrf2 system are major cellular defense mechanisms against metabolic and oxidative stress. These two systems are linked via phosphorylation of the ubiquitin binding autophagy receptor protein p62/SQSTM1 in the p62-Keap1-Nrf2 pathway. The p62-Keap1-Nrf2 pathway plays a protective role in normal cells; however, recent studies indicate that this pathway induces tumorigenesis of pre-malignant cells, and promotes the growth and drug resistance of tumor cells via metabolic reprogramming mediated by Nrf2 activation. These findings suggest that impairment of autophagy is involved in the acquisition of malignancy and maintenance of tumors, and furthermore, that p62/SQSTM1 could be a potential target for chemotherapy in cancers that harbor excess p62.